2021
DOI: 10.1021/acsenergylett.1c01395
|View full text |Cite
|
Sign up to set email alerts
|

Stack Pressure Measurements to Probe the Evolution of the Lithium–Solid-State Electrolyte Interface

Abstract: Although solid-state batteries with lithium metal could enable higher energy density and better safety characteristics than Li-ion batteries, the complex electro-chemo-mechanical evolution of the Li− solid-state electrolyte interface can diminish performance. Here, we measure the stack pressure in real time to provide new insights into the effects of applied stack pressure and electrolyte processing on the interfacial behavior of two representative solid-state electrolytes, Li 10 SnP 2 S 12 and Li 6 PS 5 Cl; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 40 publications
2
61
0
Order By: Relevance
“…The possible reason could be that the excessive stress created on electrode|electrolyte contact in a bent position helped achieve a better contact. This agrees with some other reports where pressure has been an important parameter to enhance solid-solid interface contact between Li and SSEs [83][84][85]. Wen et al also observed improvements in tensile properties and enhanced flexibility by adding 1 wt% GO to a polymer electrolyte [59].…”
Section: Go Role In Flexible Thin Film Batterysupporting
confidence: 90%
“…The possible reason could be that the excessive stress created on electrode|electrolyte contact in a bent position helped achieve a better contact. This agrees with some other reports where pressure has been an important parameter to enhance solid-solid interface contact between Li and SSEs [83][84][85]. Wen et al also observed improvements in tensile properties and enhanced flexibility by adding 1 wt% GO to a polymer electrolyte [59].…”
Section: Go Role In Flexible Thin Film Batterysupporting
confidence: 90%
“…Argyrodite type lithium phosphorus sulfide chloride (LPSCl), for example, is kinetically stable with Li metal by the SEI mainly composed of Li 2 S, Li 3 P, and LiCl, despite the narrow EW of 1.71‐2.01 V. [ 18 ] This interphase is kinetically stabilized by the ionic conducting Li 2 S and the electronic insulating Li 3 P and LiCl can ensure self‐limited reaction to avoid by‐products among the interphases. [ 84 ] But Li dendrite ingress in LPSCl still occurs. While the kinetically unstable interphase contains components with high electron conductivity, Li + is driven to form compounds but not to plate.…”
Section: Application and Design Strategies Of Hsementioning
confidence: 99%
“…SSBs in this study used custom cell housings that were calibrated to apply known amounts of stack pressure by controlling the torque applied to the cell bolts, as based on previous studies 21,40,41 . Anode-free half cells were assembled in an Ar-filled glovebox by first loading 90 mg of ground LPSC into a 10 mm PEEK die and cold pressing in a uniaxial press at 375 MPa for 1 min to form a dense pellet.…”
Section: Assembly and Testing Of Solid-state Batteriesmentioning
confidence: 99%